Efektivitas Teknik Desensitisasi Sistematis dalam Mengurangi Kecemasan Presentasi pada Kalangan Remaja: Sebuah Systematic Review - Fadillah, Siti; Maulisa, Iis; Muna, Naeila Rifatil; Maharani , Natasya (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren Cirebon, 2025)
Abstract Presentation anxiety is a form of performance anxiety commonly experienced by adolescents, both in high school and college. This condition negatively impacts self-confidence, communication skills, and academic achievement. This study aims to examine the effectiveness of the systematic desensitization technique (TDS) in reducing presentation anxiety among adolescents. The method used was a systematic review with a qualitative approach. Eight articles were analyzed, obtained through a targeted search of national databases using the keywords